The Effect Of Counseling to Modification the Lifestyle On Prevention Of Obesity In Adolescents - Anto, Anto; Sudarman, Sumardi; R, Erni Yetti; Manggabarani, Saskiyanto (PROMOTIF: Jurnal Kesehatan Masyarakat, 2017)
Obesity is a serious problem for teenagers and a global pandemic as well as the biggest chronic health problem for both advanced and developing countries. The purpose of this study is to prove the effect of counseling on lifestyle modification on obesity prevention. Design of Quasy Experiment Study "with pre-test and post-test given to the control group and modifying counseling group. Technique sample by random sampling and with formula proportional random sampling. The result showed that there was a change of normal nutrient status but there was no significant effect of counseling to modify the lifestyle to good nutrition status in treatment group (Ï=0,107) and control group (Ï = 0,081), there was change of nutrition pattern and good nutrition but there was no significant effect of counseling to modify the lifestyle to diet and good nutrition in the treatment group (Ï=0,001) and control group (Ï=0,060), physical activity no change and meaningful influence of counseling to modify lifestyle both in treatment group and control group with value (Ï=0,59). Conclusion found that lifestyle modification counseling can give enough change to nutrition status of student, diet and nutritional intake.Â Keywords : Obesity, lifestyle modification counselingÂ Â